2022
DOI: 10.1186/s12888-022-03723-7
|View full text |Cite
|
Sign up to set email alerts
|

Hip, vertebral, and wrist fracture risks and schizophrenia: a nationwide longitudinal study

Abstract: Background Fractures are a great health issue associated with morbidity, quality of life, life span, and health care expenditure. Fractures are correlated with cardiovascular disease, type 2 diabetes mellitus, cerebrovascular disease, and some psychiatric disorders. However, representative national data are few, and longitudinal cohort studies on the association between schizophrenia and the subsequent fracture risk are scant. We designed a nationwide population-based cohort study to investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…In addition, our findings were identified on heel eBMD which did not represent BMD, despite ultrasound eBMD was increasingly recognized as a valid alternative to DXA [ 46 ] and successfully wielded in previous studies [ 16 , 18 , 47 ]. Though previous observational studies believed that schizophrenia would increase the risk of fracture and reduce BMD [ 5 , 29 , 48 ], our results still needed to be confirmed in future studies. Finally, only BMI was considered in MVMR as it was mostly correlated with the selected IVs, but the effects of other confounding factors such as age, and vitamin D were not included, which was worth further investigated.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In addition, our findings were identified on heel eBMD which did not represent BMD, despite ultrasound eBMD was increasingly recognized as a valid alternative to DXA [ 46 ] and successfully wielded in previous studies [ 16 , 18 , 47 ]. Though previous observational studies believed that schizophrenia would increase the risk of fracture and reduce BMD [ 5 , 29 , 48 ], our results still needed to be confirmed in future studies. Finally, only BMI was considered in MVMR as it was mostly correlated with the selected IVs, but the effects of other confounding factors such as age, and vitamin D were not included, which was worth further investigated.…”
Section: Discussionmentioning
confidence: 67%
“…Our study also found that schizophrenia had a genetic causal effect on the fracture of femur which was a position of the hip joint fracture. A recent 10-year cohort study suggested that the risk of hip fracture in schizophrenic patients was higher than that in the control group, while no difference was found in wrist fracture [ 5 ]. The evidence of schizophrenics prone to hip fractures compared to the general population also existed in a large population-cohort study [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DM is prevalent worldwide and affects the quality of life of many patients. Major factors, including genetics, diets, lifestyle, stress, and environments, are considered to be closely related to the development of DM. Recently, emerging evidence has clearly demonstrated that gut microbiota may play a role in regulating an inflammatory response and insulin resistance through the actions of their metabolites (Figure ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Stubbs et al ( 14 ) found that people with schizophrenia have a 50–100% increased risk of fracture compared to people without mental illness. Chu et al ( 15 ) found a significantly higher risk for hip and vertebral fractures in people with schizophrenia compared to controls. Zhu et al ( 16 ) recently showed that elevated depressive symptoms in Chinese people are associated with an increased risk for falls and hip fractures.…”
Section: Introductionmentioning
confidence: 99%